2007
DOI: 10.1111/j.1528-1167.2007.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Neuronal Networks Are Associated with Spikes and Slow Activity in Hypsarrhythmia

Abstract: SUMMARYPurpose: West syndrome is a severe epileptic encephalopathy of infancy characterized by a poor developmental outcome and hypsarrhythmia. The pathogenesis of hypsarrhythmia is insufficiently understood. Methods: We investigated eight patients with infantile spasms and hypsarrhythmia (group I) and 8 children with complex partial seizures (group II) using simultaneous recordings of electroencephalogram (EEG) and functional MRI. Hemodynamic responses to epileptiform discharges and slow wave activity (EEG de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 54 publications
(82 reference statements)
9
73
1
Order By: Relevance
“…Studies on functional neuroimaging mostly with PET technology in West syndrome have revealed putamen, brainstem and various cortical regions playing an important role in the pathogenesis of hypsarrhythmia (Chugani et al, 1990, Haginoya et al, 2000, Hrachovy et al, 1981, Morimatsu et al, 1972, Metsahonkala et al, 2002, Neville, 1972, Satoh et al, 1986, Hrachovy and Frost, 2003. Using simultaneous EEG-fMRI recordings, Siniatchkin et al (2007) have demonstrated recently, that the high-amplitude slow cortical activity in hypsarrhythmia is associated with positive BOLD effects in putamen and brainstem, and that multifocal epileptiform discharges are correlated with positive BOLD effects in occipital cortex and various other cortical areas.…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on functional neuroimaging mostly with PET technology in West syndrome have revealed putamen, brainstem and various cortical regions playing an important role in the pathogenesis of hypsarrhythmia (Chugani et al, 1990, Haginoya et al, 2000, Hrachovy et al, 1981, Morimatsu et al, 1972, Metsahonkala et al, 2002, Neville, 1972, Satoh et al, 1986, Hrachovy and Frost, 2003. Using simultaneous EEG-fMRI recordings, Siniatchkin et al (2007) have demonstrated recently, that the high-amplitude slow cortical activity in hypsarrhythmia is associated with positive BOLD effects in putamen and brainstem, and that multifocal epileptiform discharges are correlated with positive BOLD effects in occipital cortex and various other cortical areas.…”
Section: Pathogenesismentioning
confidence: 99%
“…In order to evaluate the specificity of pathogenetic mechanisms of hypsarrhythmia, these infants were compared with children suffering from complex partial seizures. In order to validate the results obtained with DICS, we compared the results of electrical source imaging with EEG -fMRI results obtained previously from the same data sets of EEG-fMRI recordings (Siniatchkin et al, 2007).…”
Section: Aims Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…EEG-fMRI studies have recently contributed to the understanding of the epileptic networks involved in different epileptic encephalopathies (EEs). To date, studies have been published in continuous spike-and-wave during sleep (CSWS), Lennox-Gastaut syndrome (LGS), and West (WS) syndromes, [11][12][13][14] revealing the existence of specific networks involved during the pathologic activity in such conditions. In [r (20)] syndrome, we recently showed that the typical theta-delta rhythm is generated within the frontoparietal cortices, suggesting a dysfunction of the premotor/sensorimotor systems.…”
mentioning
confidence: 99%